Grazing rates of a calanoid copepod (Paralabidocera antarctica) in a continental Antarctic lake - Kerrie Swadling; Gibson, JAE (2000)
The presence of crustaceans in some Antarctic lakes adds a level of complexity to the food webs of these environments. The grazing pressure of the crustaceans on phytoplankton and other protists, and the role they play in controlling food web structure, has not yet been examined in any detail. This paper presents the first data on grazing pressure of crustacean zooplankton in continental Antarctic lakes. In this study the grazing rates of Paralabidocera antarctica in saline Ace Lake, Vestfold Hills, were assessed using a radio-tracer method. Clearance rates ranged from approximately 1 to 8 ml ind. -1 day -1 , depending on developmental stage. Due to their high abundance, nauplii exhibited the highest daily carbon ingestion rates. The population cleared about 3% of the water column per day, accounting for a significant fraction of primary production. P. antarctica has a considerable impact on the carbon cycle in Ace Lake and, by inference, in the other lakes in which it occurs.